IMPROVING THE METHODOLOGY OF DETERMINING THE RATING AND RANKING OF REAL ESTATE ORGANIZATIONS - Tashpulatov Giyos Tokhirovich (American Journals, 2023)
In this article, the application of the methodology for determining the rating of real estate organizations in Uzbekistan and the creation of a toroidal model of the interdependence of the activities of rating agencies are discussed and suggestions are made. The necessary legal framework and economic conditions for the functioning mechanism of this market are being gradually created. However, in Uzbekistan, the impact of macroeconomic policy on REM and the role of this market in the national economy has not been analytically evaluated, and the problems of evaluating the rating of real estate organizations operating in it have not been sufficiently resolved. However, in the world, REM and real estate services are of great importance for the economy and are a driver of development for many related industries.
Keywords: real estate market (REM), the functioning mechanism, problems of evaluating, ownership system, rating scale standards, rating agencies